Faktor yang Mempengaruhi Perilaku Seksual Pranikah pada Remaja di Indonesia - Kartika Adyani; Diana Qomariyah; Meilia Rahmawati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Problems that are often experienced by adolescents today are problems around sexuality, especially premarital sex The formation of premarital sexual behavior resulting in various impacts on health is influenced by several factors that affect sexual behavior in adolescents, especially in Indonesia. The techniques include a national and international litrature review through the use of key words and selections based on predetermined inclusion and exclusion criteria, as well as 10 articles, 8 of which were published in national journal and 2 of which were published in international journals. The health behavior of a person or community is formed from three main factors, namely predisposing factors, enabling factors, and reinforcing factors, several factors that influence sexual behavior, namely knowledge, information media, parental attitudes, peers. that there are factors that influence the use of premarital sexual behavior in adolescents in Indonesia, many of which are influenced by predisposing factors, namely knowledge and attitudes, the second supporting factor is the role of parents and the third driving factor is the influence of peers.